FONA-7, a Novel Extended-Spectrum β-Lactamase Variant of the FONA Family Identified in Serratia fonticola - Fuentes Castillo, Danny (2020)
Serratia fonticola is a human pathogen widely found in the environment, with birds being reported as possible natural hosts. During an epidemiological and genomic surveillance study conducted to monitor the occurrence of extended-spectrum b-lactamase (ESBL)-producing Enterobacterales in South American wild birds, we identiﬁed an ESBL-positive S. fonticola in a fecal sample collected from a Hudsonian Whimbrel, during its non-breeding range on the Paciﬁc Coast of Chile. Whole genome sequencing analysis and in silico modeling revealed a novel variant of the class A ESBLs FONA family, designated FONA-7, which shows 96.28% amino acid identity with FONA-6; with amino acid substitutions occurring in the signal peptide sequence (Thr22/Ser), and in the mature protein (Ser39/Asn and Thr227/Ile). This ﬁnding denotes that migratory birds can be potential vectors for the transboundary spread of ESBL-producing bacteria, creating a further theoretical riskfor the origin of novel plasmid-encoded b-lactamases.